The carefully considered rape of the world - Mead, Shepherd; Ace Books (New York : Ace, 1965)
This is the story of women becoming inexplicably pregnant. And it happens to every type of woman, regardless of race or creed, from nuns to lesbians. It happened to Beauford Abel's wife. With her, a perfume tester called; one of his more exotic samples made her black out for a split second. At least she thought it was a split second... When Beauford eventually figures out what's going on, he plays amateur sleuth. But instead of finding sex maniacs, he finds brainy apes planning to invade the earth. And the brainy apes are clever enough to ask Beauford to handle their PR. They'd like to be liked when they land. And they'd like the baby apes that earth women will soon be giving birth to, to be liked as well. You might think this is a pretty funny way for invaders to act. In this book, everything's funny.
Mode of access: Internet.
Keywords: Science fiction